MENERAPKAN NILAI-NILAI PEMIKIRAN DEWI SARTIKA DALAM PENDIDIKAN MODERN - Tahimu, Muhammad Reza (Musawa: Journal for Gender Studies, 2024)
Dewi Sartika, a national hero of Indonesia, is known as a pioneer of education for women. Her thoughts on education are still relevant today, amidst the modern era full of challenges and changes. The values of Dewi Sartika's thoughts, such as noble character, intelligence, and independence, can be a guide in implementing quality and character-based education in the modern era. This study aims to identify the values of Dewi Sartika's thoughts on education and analyze their relevance in modern education. The research method used is a qualitative research method with a literature study approach. Data was collected through literature studies, including books, scientific journals, online articles, and official documents. The data were then analyzed using a descriptive-analytic method. The results of the study show that the values of Dewi Sartika's thoughts on education are still relevant in modern education. These values can be implemented in various ways, such as integrating moral values and noble character into the curriculum and learning, developing character education through various programs and activities, providing opportunities for students to learn independently and creatively, and utilizing information and communication technology to support learning. There are also challenges and opportunities in implementing the values of Dewi Sartika's thoughts on education in modern education. The challenges include globalization and the influence of foreign cultures that can erode local cultural values, a lack of awareness and commitment from various parties to implement character education, and limited educational resources and infrastructure. However, there are also opportunities, such as increasing public awareness of the importance of character education, the development of information and communication technology that can support learning, and support from the government and various parties to improve the quality of education. Keywords: education, character education, modern education, Indonesia